Carbon nanomaterials for advanced energy systems : advances in materials synthesis and device applications - Lu, Wen; e; Dai, Liming (Hoboken, New Jersey : Wiley, 2015)
With the proliferation of electronic devices, the world will need to double its energy supply by 2050. This book addresses this challenge and discusses synthesis and characterization of carbon nanomaterials for energy conversion and storage. Addresses one of the leading challenges facing society today as we steer away from dwindling supplies of fossil fuels and a rising need for electric power due to the proliferation of electronic products Promotes the use of carbon nanomaterials for energy applications Systematic coverage: synthesis, characterization, and a wide array of carbon nanomaterials are described Detailed descriptions of solar cells, electrodes, thermoelectrics, supercapacitors, and lithium-ion-based storage Discusses special architecture required for energy storage including hydrogen, methane, etc.
Keywords: Materials for Energy Systems; Nanomaterials; Organic Chemistry; Electronic books